Management of innovation, performance and added value : a case study In the agrobusiness chain - Büttendender, Pedro Luis (2021)
Fil: Büttendender, Pedro Luis. Universidade do Noroeste do Estado do RS. Departamento de Estudios de Administración; Brasil.